Pan‐European early switch/early discharge opportunities exist for hospitalized patients with methicillin‐resistant Staphylococcus aureus complicated skin and soft tissue infections. (15th May 2014) - Nathwani, D.; Eckmann, C.; Lawson, W.; Stephens, J. M.; Macahilig, C.; Solem, C. T.; Simoneau, D.; Chambers, R.; Li, J. Z.; Haider, S.; Paul, M.
Abstract The objective of this study was to document pan‐European real‐world treatment patterns and healthcare resource use and estimate opportunities for early switch (ES) from intravenous (IV) to oral antibiotics and early discharge (ED) in hospitalized patients with methicillin‐resistant Staphylococcus aureus (MRSA) complicated skin and soft tissue infections (cSSTIs). This retrospective observational medical chart review study enrolled 342 physicians across 12 European countries who collected data from 1542 patients with documented MRSA cSSTI who were hospitalized (July 2010 to June 2011) and discharged alive (by July 2011). Data included clinical characteristics and outcomes, hospital length of stay (LOS), MRSA‐targeted IV and oral antibiotic use, and ES and ED eligibility according to literature‐based and expert‐validated criteria. The most frequent initial MRSA‐active antibiotics were vancomycin (50.2%), linezolid (15.1%), clindamycin (10.8%), and teicoplanin (10.4%). Patients discharged with MRSA‐active antibiotics (n = 480) were most frequently prescribed linezolid (42.1%) and clindamycin (19.8%). IV treatment duration (9.3 ± 6.5 vs. 14.6 ± 9.9 days; p <0.001) and hospital LOS (19.1 ± 12.9 vs. 21.0 ± 18.2 days; p 0.162) tended to be shorter for patients switched from IV to oral treatment than for patients who received IV treatment only. Of the patients, 33.6% met ES criteria and could have discontinued IV treatment 6.0 ± 5.5 days earlier, and 37.9% met ED criteria and could have been discharged 6.2 ± 8.2 days earlier. More than one‐third of European patients hospitalized for MRSA cSSTI could be eligible for ES and ED, resulting in substantial reductions in IV days and bed‐days, with potential savings of €2000 per ED‐eligible patient.